2019
DOI: 10.1002/cam4.2361
|View full text |Cite
|
Sign up to set email alerts
|

Significantly increased anti‐tumor activity of carcinoembryonic antigen‐specific chimeric antigen receptor T cells in combination with recombinant human IL‐12

Abstract: Background aims Chimeric antigen receptor T cells (CAR‐T cells) have been successfully used in treatments of hematological tumors, however, their anti‐tumor activity in solid tumor treatments was limited. As IL‐12 increases T‐cell immune functions, we designed carcinoembryonic antigen (CEA) specific CAR‐T (CEA‐CAR‐T) cells and, for the first time, used them in combination with recombinant human IL‐12 (rhIL‐12) to treat several types of solid tumors. Methods In vitro ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Interestingly, there were no CAR-T related severe adverse events observed among all the 10 patients involved in this study (150). Furthermore, combination treatment between CEA-CAR-T cells in addition to recombinant human interleukin 12 (rh-IL12) in mouce models show effective and elevated anti-tumor activity of CAR-T cells among various types of solid tumors including CRC (151).…”
Section: Adoptive Cell Transfer (Act)mentioning
confidence: 82%
“…Interestingly, there were no CAR-T related severe adverse events observed among all the 10 patients involved in this study (150). Furthermore, combination treatment between CEA-CAR-T cells in addition to recombinant human interleukin 12 (rh-IL12) in mouce models show effective and elevated anti-tumor activity of CAR-T cells among various types of solid tumors including CRC (151).…”
Section: Adoptive Cell Transfer (Act)mentioning
confidence: 82%
“…the Tn and STn antigens on MUC1, has already been shown to inhibit the growth of PDAC cell lines [ 169 ] and control PDAC xenograft growth in murine models [ 170 ]. The combination of CEA-CAR-T with rhIL-12 exerted significant antitumour effects in vitro and in vivo [ 171 ], and a phase II/III trial (NCT04037241) to evaluate the efficacy of CEA-CAR-T is recruiting patients. CD133 is a marker of cancer stem cells and is related to tumour metastasis and recurrence; a phase I trial (NCT02541370) confirmed the safety of CAR-T-133 in patients with advanced metastatic malignancies [ 172 ].…”
Section: The Immunosuppressive Microenvironment and Immunotherapy Inmentioning
confidence: 99%
“…Optimal T cell activation, amplification, and persistence require not only antigen engagement (signal 1) and costimulatory signals (signal 2), but also cytokine support (signal 3). However, signal 3 is deficient in the TME, which hampers the full activation of T cells [61]. Therefore, constructing CAR T cells that can provide signal 3 will help promote their activation and proliferation.…”
Section: Cytokine Strategymentioning
confidence: 99%